POLITICAL EFFECT IN MERDEKA BELAJAR EDUCATION ERA OF THE COVID-19 PANDEMIC - Kang Heri; Zaini Zaini (Nurul Jadid University, 2021)
Political influence in education is like compulsory instruction, while it is difficult to create without astute individuals. Even the brightest individuals have to be framed through school. Education is directly or by implication influenced by government issues. The amalgamation of instructions and governance issues is plural. For a while, teaching can shape people who participate in political life. The reason for the school is to make students mentally minded and have great personalities. The training framework must produce millennial students who can compete in the modern-based 4.0 era. Therefore, the educational framework in Pamekasan continues to improve and change. Changes in schooling began with Nadiem Makarim's discourse, who proposed the development of